PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI SISWA KORBAN BULLYING - Jumiati Jumiati; Adhelmi Adhelmi; Yuyun Yuniar; Indah Wigati (Raudhah - Proud To Be Professional, 2023)
This study aims to determine the role of Guidance and Counseling Teachers in overcoming students who are victims of bullying at MTs Negeri 4 Musi Banyuasin school. This research uses a type of qualitative research that is descriptive. The subject of this study is Guidance and Counseling Teacher . Data collection techniques used by researchers are observation, interviews, and documentation. The subjects used in the researcher were 4 people. Based on the results of the study, it can be concluded that the role of guidance and counseling teachers in overcoming students victims of bullying at MTs Negeri 4 Musi Banyuasin school is the first preventive action by providing understanding and knowledge about bullying through classical guidance. Perform curative actions, namely identifying problems by looking for data on the background causes of problems so that BK teachers can provide counseling services by motivating victims of bullying. Carry out development actions by working with community stores, parents to monitor behavior outside of school and working with homeroom teachers, subjects to provide supervision within the school with the aim that bullying does not occur again.